A new skink of the genus Subdoluseps (Hardwicke & Gray, 1828) from Peninsular Malaysia - Grismer, L. Lee; Dzukafly, Zaharil; Muin, Mohd Abdul; Quah, Evan S. H.; Karin, Benjamin R.; Anuar, Shahrul; Freitas, Elyse S. (Zootaxa, 2019)
An integrative taxonomic analysis of Subdoluseps herberti from southern Thailand and Peninsular Malaysia and S. samajaya from Sarawak, East Malaysia (Borneo) recovers the former as paraphyletic with respect to the latter. The analyses recover the three southernmost populations of S. herberti in Peninsular Malaysia as conspecific and the sister lineage of S. samajaya, whereas S. herberti from Thailand and northern Peninsular Malaysia constitute the sister species to S. samajaya plus the southern three Peninsular Malaysian populations. As such, the southern populations are described herein as S. malayana sp. nov. and all three species are referred to as the S. herberti group. Clade boundaries and breaks within this group on the Thai-Malay Peninsula occurring at the Isthmus of Kra, across the Kangar-Pattani line, and between the Thai-Malay Peninsula and Borneo are consistent with phylogeographic patterns of other Sundaic taxa. The discovery of S. malayana sp. nov. continues to underscore the fact that, despite the well-studied nature of the lizard fauna of Peninsular Malaysia, much of it still remains unrealized and for conservation efforts to move forward, field research followed by expeditiously revised taxonomies must continue.